1996
DOI: 10.1128/mcb.16.7.3401
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Regulation of the Murine Cyclin E Gene Depends on an E2F Binding Site in the Promoter

Abstract: Cyclin E controls progression through the G 1 phase of the cell cycle in mammalian fibroblasts and potentially in many other cell types. Cyclin E is a rate-limiting activator of cdk2 kinase in late G 1 . The abundance of cyclin E is controlled by phase-specific fluctuations in the mRNA level; in mammalian fibroblasts, mRNA is not detected under conditions of serum starvation and is accumulated upon serum stimulation, with expression starting in mid-G 1 . Here, we report the cloning of the murine cyclin E promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
210
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(217 citation statements)
references
References 32 publications
7
210
0
Order By: Relevance
“…The presence of oncogenic Ras does not alter the amount of cyclin E either in absence or in presence of FCS. Since the cyclin E promoter contains E2F binding sites (Botz et al, 1996), the lack of induction of cyclin E expression by oncogenic Ras is consistent with the ®nding that Ras cannot inactivate pRb. Our results show that in serum-starved cells cdk2 is associated with cyclin E and that this association increases 9 h after serum stimulation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The presence of oncogenic Ras does not alter the amount of cyclin E either in absence or in presence of FCS. Since the cyclin E promoter contains E2F binding sites (Botz et al, 1996), the lack of induction of cyclin E expression by oncogenic Ras is consistent with the ®nding that Ras cannot inactivate pRb. Our results show that in serum-starved cells cdk2 is associated with cyclin E and that this association increases 9 h after serum stimulation.…”
Section: Discussionsupporting
confidence: 79%
“…The hypophosphorylated form of these proteins binds the transcription factor E2F, and upon phosphorylation, E2F is released and can activate transcription of S phase-speci®c genes (Draetta, 1994;Lam and La Thangue, 1994;Mittnacht, 1998). Among the genes containing E2F-binding sites in their promoter regions there are those coding for enzymes and proteins that are essential for DNA replication such as DNA polymerase a, thymidin kinase, ribonucleotide reductase, cyclin A and cyclin E (Botz et al, 1996;Dalton, 1992;Dou et al, 1994;Geng et al, 1996;Zwicker et al, 1995). The activation of cyclin D/cdk4 and phosphorylation of pRb is thus a limiting step for G1 progression.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin E is a direct target gene of E2F1 (DeGregori et al, 1995;Botz et al, 1996). We found that Tam67 suppressed cyclin E mRNA at all time points examined, showing a 30-60% suppression (P ¼ 0.0005) (Figures 5a and b).…”
Section: E2f Target Genes Are Regulated Upon Ap-1 Blockadementioning
confidence: 81%
“…The promotor of the cyclin E gene has been isolated and analysed by several groups and was shown to contain multiple potential E2F binding sites. Transcriptional regulation indeed depends on the presence of these E2F binding sites and on the presence and function of Rb (Botz et al, 1996;Geng et al, 1996;Ohtani et al, 1995). In addition to the regulation of cyclin E or cyclin D expression through the modulation of the promotor, the enzymatic activity of D-and E-type cyclin/CDK complexes is regulated independently on a posttranscriptional level.…”
Section: Introductionmentioning
confidence: 99%